Dari Desa Nelayan Sampai Desa Wisata Studi Historis Desa Wisata Pemuteran Dan Potensinya Sebagai Sumber Belajar Sejarah Di SMA - Anjali, Alina Ratna; Yasa, I Wayan Putra; Purnawati, Desak Made Oka (Universitas Pendidikan Ganesha, 2023)
This study aims to find out: (1) the background of Pemuteran Village changed from a fishing village to a tourist village, (2) the dynamics of tourism development in Pemuteran Village, (3) find out the development of tourism in Pemuteran Village which can be used as a source of history learning in high school. The research method used is historical research with a qualitative approach including: (1) heuristics, (2) source criticism or verification, (3) interpretation, and (4) historiography. The results of the study show that: the historical development that occurred in Pemuteran Village from being a fisherman to being a tourism actor. Pemuteran Village can develop in the tourism sector which is supported by the attractiveness of marine tourism. The development of tourism in Pemuteran Village has an impact, namely increasing the economy of the people who are tourism actors. As for the potential from fishing villages to tourist villages, study the history of Pemuteran Tourism Village and its potential as a source of learning history in high school: historical aspects, educational character aspects, socio-cultural aspects and environmental aspects.